(untitled) (CAHIERS MAGELLANES-NS, 2024)
In this paper we established integral formulas involving K-generalized Mittag-Leffler function and result is transform in terms of generalized beta and gamma function. Some interesting transforms of our main results are also considered. The results are derived with the help of an interesting integral due to Lavoie and troitter